RANCANG BANGUN SISTEM SMART HOME PADA RUMAH KOS BERBASIS INTERNET OF THINGS - Gede Prananda Putra; Yoga Divayana; Pratolo Rahardjo (Program Studi Teknik Elektro UNUD, 2022)
Technological developments in the field of electronics to date have made the humanmindset advanced in the application of electronic equipment. One example of its development isremote control of electrical equipment. Many people use these developments as a means offacilitating life activities in solving problems that occur. The use of the internet in life can beused as an example in the use of technological developments. The internet is one of thecommunication media that has many benefits in increasing effectiveness, work efficiency, andmonitoring. The internet can be used as a transmission medium for control and monitoringsystems. With the internet, one can control electrical equipment and monitor the condition of thehouse. The concept originated from the Internet of Things or IoT. IoT is a concept where alltools and services in the system are connected to each other using internet media. Based onthese problems, a smart home system was created that functions as control of electricalequipment, smoke detection, monitoring of temperature and humidity in the room. Themonitoring and control system is integrated with Android applications and based on the Internetof Things.